Extratos padronizados para o tratamento de doenças crônicas: Arrabidaea spp - Rocha, Claudia Quintino da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The project aimed to standardize extracts to treat most prevalent chronic diseases in our population. The specie investigated was Arrabidaea brachypoda (Bignoniaceae), genus of which are reported various pharmacological activities. Leaves and barks of the roots were dried in an oven. The obtained powders were percolated each part with 70% ethanol v / v, the mixture was filtered and concentrated on rotaevaporator. The extracts were subjected to clean-up cartridges Sep-Pak reverse phase and analyzed by HPLC-PDA. The chromatographic profiles showed that both are rich in phenolic substances. Fractionation of the extract of the roots provided novel compounds 7, 6 of them rare dimeric flavonoids, being a majority of them in the extract. This substance served as a marker for standardization of the extract. Fractionation of leaf extract provided 13 substances, 10 of them reported here for the first time in this species. Rutin is a majority in this extract and was used as a marker for standardization of the same. Biological assays showed that extracts and compounds of A.brachypoda possess anti-inflammatory activity, anti-gastric ulcer and anti-protozoa. This project resulted in two international patent applications.

O projeto teve como objetivo padronizar extratos para tratar doenças crônicas mais prevalentes na população brasileira. A espécie investigada foi Arrabidaea brachypoda (Bignoniaceae), gênero do qual são relatadas várias atividades farmacológicas. Folhas e cascas das raízes foram secas em estufa. Os pós obtidos de cada parte foram percolados com etanol 70% v/v, a mistura foi filtrada e concentrada em rotaevaporador. Os extratos obtidos foram submetidos a clean-up em cartuchos Sep-Pak de fase reversa e analisados por HPLC-PDA. Os perfis cromatográficos mostraram que ambos são ricos em substâncias fenólicas. Fracionamento do extrato das raízes forneceu 7 substâncias inéditos dentre eles 6 flavonóides diméricos raros, sendo um deles majoritário no extrato. Esta substância serviu de marcador para padronização do extrato. Fracionamento cromatográfico do extrato das folhas forneceu 13 substâncias, 10 delas relatatas aqui pela primeira vez na espécie. A rutina é majoritária nesse extrato e foi usada como marcador para padronização do mesmo. Ensaios biológicos demonstraram que os extratos e substâncias de A.brachypoda possuem atividade anti-inflamatória, anti-úlceras gástricas e anti-protozoários. Este projeto resultou em dois pedidos de patentes internacionais.
Keywords: Quimica organica; Química vegetal; Normalização; Chemical plant